Anti-biofilm peptide combinations in the eradication of pre-established biofilms of Pseudomonas aeruginosa and Staphylococcus aureus - Jorge, Paula Alexandra Silva (2015)
The emergence of resistance is a preoccupant health threat and the development of new strategies and the use of novel compounds are in demand. Specifically, biofilm infections are a serious threat, causing chronic, nosocomial and biomaterial related infections, being related to dissemination of antibiotic resistance. Pseudomonas aeruginosa and Staphylococcus aureus are great developers of resistance and their ability to form biofilms makes them responsible for severe chronic infections. In this work, we associated the use of novel compounds antimicrobial peptides (AMPs) with a combination strategy. The AMP/antibiotic colistin was combined with three other AMPs (linear tachyplesin I; temporin A; citropin 1.1). Previous results showed the ability of these AMPs to combine synergistically against these bacteria. Here, we test these combinations against single pre-established biofilms and the results show promise. Currently, we are testing these combinations on mixed biofilms to assess their use in polymicrobial infections.